Conflicts Of Public Infrastructure In Peri-Urban Area - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Abstract: Rapid population growth and development of urban area will affect to surrounding area and will change area condition from rural to urban. During the process of transformation, usually called "Urbanization", will generate conflicts of public infrastructure function such as drainage, irrigation, and road system. Identification of these transformation could be as follows: (a) changing function from irrigation to drainage system, (b) increasing of drainage system density, (c) increasing of road system density, (d) criteria of land use will be more sensitive to water inundation, and (e) increasing of sanitation problems. Those conflict will create 3-E crisis as follows: (a) environmental crisis (such as pollution and public health deterioration, lack of domestic water available), (b) economic crisis (such as increasing of flood, risk of infrastructure malfunction and decreasing of land value) and (c) equity crisis due to social crisis between upstream and downstream area. The 2-E strategy to overcome crisis may be applied, i.e., (a) engineering aspect (application of appropriate technology based on physical regime), and (b) education aspect (community based development), while an additional strategy to applied is strengthening of law enforcement.